Mobilité des étudiants sud-américains : le cas du programme ESCALA - Maria Alice Nogueira; Viviane Ramos (Cahiers de la Recherche sur l'Education et les Savoirs, 2014)
This article focuses on ESCALA, a mobility student program created in 2000 for students of 28 public universities from Argentina, Brazil, Bolivia, Chile, Paraguay, and Uruguay. Through it, undergraduate students can study 6 months in one of the partner universities, with almost all expenses covered. Data analysis shows a growth in the number of participants over the years. This group is composed by 58.58% of women, 41.03% from Humanities and Social Sciences, and has Argentina and Brazil as their main destination. Interviews conducted with Brazilian participants show that students see Latin American as their « possible» destination, not as the most desirable one, what would be the North countries. Furthermore, there seems to be a preference for certain universities and countries, considered as “more developed” within the group.